Correlation of demographic, histological and molecular characteristics and clinical course of the disease in patients with lung adenocarcinoma - Lora Novaković Lacković; Ljilja Latinović Tadić; Mirko Stanetić; Nataša Tanasković; Slavica Marić; Marko Lacković (Medicinski glasnik, 2019)
Aim: Retrospective analysis of disease clinical course with a purpose of defining potential prognostic parameters which are essential for optimal target therapy. Methods: The study involved 29 patients with histologically confirmed lung adenocarcinoma and existing epidermal growth factor receptor (EGFR) mutations, which are treated by tyrosine kinase inhibitors (TKI). Results: Allegations of a larger prevalence in women and non-smokers were found. The study confirmed dominance of mutations on exon 19 and exon 21. Usefulness of the treatment with erlotinib in terms of increasing survival time was evident. Median survival of patients in the survey sample was 14.5 months. Median survival in relation to gender or smoking status did not show statistical significance. Conclusion: Considering obtained results, we have confirmed that patients with advanced lung adenocarcinoma and present mutations of epidermal growth factor receptor, who had been treated with first generation TKI, had median survival time of over a year.
Keywords: epidermal growth factor; mutation; reaction time; receptor